2019
DOI: 10.20546/ijcmas.2019.803.252
|View full text |Cite
|
Sign up to set email alerts
|

Haemonchus contortus Infection and Associated Pathological Changes in a Goat (Capra hircus)

Abstract: The animal had emaciated body, pale mucous membranes with the history of anorexia and loss of body weight. Upon necropsy, the internal organs were found extremely pale, which was suggestive of anaemia. Liver of the animal was hemorrhagic and enlarged. Abomasum of the animal was found filled with the blood-sucking parasites Haemonchus contortus spp. and severe abomasitis was observed. Fecal sample collected for microscopic examination revealed 1150 egg per gram indicating severe parasitic infestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Galiza et al, (2011) [5] reported watery blood, pale tissues, and the presence of liquid in the peritoneal and pericardial cavity. Patel et al, (2019) [11] noticed serous exudates were found in the abdominal cavity. In heart hydropericardium, gelatinisation of epicardial fat (Fig.…”
Section: Internal Examinationmentioning
confidence: 98%
See 1 more Smart Citation
“…Galiza et al, (2011) [5] reported watery blood, pale tissues, and the presence of liquid in the peritoneal and pericardial cavity. Patel et al, (2019) [11] noticed serous exudates were found in the abdominal cavity. In heart hydropericardium, gelatinisation of epicardial fat (Fig.…”
Section: Internal Examinationmentioning
confidence: 98%
“…1). Post mortem examination showed extreme pale viscera indicating severe anaemia (Patel et al, 2019) [11] . Discharges from nostrils, sunken eye balls in few sheep and goats, gelatinisation of abdominal, sub cutaneous (Fig.…”
Section: External Examinationmentioning
confidence: 99%